OPTIMIZATION OF STRUCTURAL ELEMENTS OF THREE PART STATIONS TAKING INTO ACCOUNT THE SPECIFICS OF THEIR BEHAVIOR - Tiutkin, O. L.; Petrenko, I. M. (Science and Transport Progress, 2004)
The article provides the analysis of optimization concept of constructive elements in three-vaulted deep contour underground stations. Statement of the optimization task has been performed; its solution and algorithm of its realization have been presented.